HIF prolyl and asparaginyl hydroxylases in the biological response to intracellular O(2) levels. - Masson, N; Ratcliffe, P (2003)
Hypoxia-inducible factor (HIF) is a heterodimeric transcription factor that plays a crucial role in mediating cellular responses to oxygen. Oxygen availability influences multiple steps in HIF activation and recent studies have indicated that at least two steps in this process are governed by a novel mode of signal transduction involving enzymatic hydroxylation of specific amino acid residues in HIF-alpha subunits by a series of 2-oxoglutarate (2-OG)-dependent oxygenases. These enzymes are non-haem iron enzymes that use dioxygen in the hydroxylation reaction and therefore provide a direct link between the availability of molecular oxygen and regulation of HIF. Prolyl hydroxylation regulates proteolytic destruction of HIF-alpha by the von Hippel-Lindau ubiquitin ligase complex, whereas HIF-alpha asparaginyl hydroxylation regulates recruitment of transcriptional coactivators. The involvement of at least two distinct types of 2-OG-dependent oxygenase in oxygen-regulated transcription suggests that these enzymes may be well suited to a role in cellular oxygen sensing.